2014
DOI: 10.1007/s00330-014-3152-7
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of the surrounding tissue of breast lesions evaluated by ultrasound elastography

Abstract: • Stiffness of the surrounding tissue of malignant breast lesions was increased. • Stiffness of the surrounding tissue correlated with stiffness of breast lesions. • Stiffness of the surrounding tissue has potential use in diagnosis of breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 61 publications
7
32
2
Order By: Relevance
“…These cut off points yielded the highest sensitivities of 83.3, 77.7 and 95.8% for UE, MRI and UE+MRI, respectively. Previous studies reported similar results, observing that the sensitivity of UE ranged between 87.1 and 95.0% in the diagnosis of breast cancer (19,21). Furthermore, the present study revealed that the accuracy rates of differential diagnosis were 82.5, 75.5 and 95.3% for UE, MRI and UE+MRI, respectively.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These cut off points yielded the highest sensitivities of 83.3, 77.7 and 95.8% for UE, MRI and UE+MRI, respectively. Previous studies reported similar results, observing that the sensitivity of UE ranged between 87.1 and 95.0% in the diagnosis of breast cancer (19,21). Furthermore, the present study revealed that the accuracy rates of differential diagnosis were 82.5, 75.5 and 95.3% for UE, MRI and UE+MRI, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…MRI is another noninvasive diagnostic tool that is useful in distinguishing soft tissue from other tissues. Therefore, the combination of UE and MRI may be more beneficial to identify the likelihood of benign or malignant breast lesions based on the hardness of the lesions (18,19). As a novel and effective imaging tool, the combination of UE and MRI methods may significantly improve diagnostic accuracy and be more objective.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (40) the grade of peritumoral edema identified in breast MRI has been independently associated with disease recurrence. In study by Zhou et al (41), it was demonstrated that the peritumoral stiffness assessed by ultrasound elastography of malignant breast lesions was higher than that of benign lesions. A 2017 study (17) was the first attempt to extract radiomics features from both intratumoral and peritumoral regions in breast DCE-MRI, where the features successfully predicted the pathological complete response to neoadjuvant chemotherapy.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 97%
“…Ultrasonography has become an important tool in neoplasm evaluation and, when combined with mammography, can aid in the diagnosis, differentiation, and prediction of malignancy in mammary tumors in human medicine [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%